Numerical experiments with the newton flow algorithm for parameter estimation in S-systems - De Paz, Margie Tacusalme
Parameter estimation is still a major challenge in modeling biochemical systems. Although experimental techniques have been rapidly improving and are now providing quantitative dynamic data that are unheard of a few years ago, fitting the model to these dynamic data still involves a lot of guess work. The main difficulty is the highly non-linear nature of the mathematical models of biochemical systems. The usual strategy done by modelers is to employ different types of algorithms and computational scientists are still looking for the silver bullet that can solve the optimization problems arising from parameter estimation in biochemical system models. A numerical method was recently proposed by Kutalik et.al. (IET Systems Biology 2007) which seems to work for a wide range of S-system models.